The Use of Volitional Strategies to Foster Students’ Reading Motivation - Achmad Bernhardo Elzamzami (P-SEMART JOURNAL, 2022)
This study was aimed to describe the teacher’s implementations and the students’ perceptions in the use of volitional strategy to foster students’ reading motivation at SMPN 54 Surabaya. As this study was aimed to describe the findings, it was identified as a descriptive qualitative study. The subjects of this study were 7I class of SMPN 54 Surabaya the researcher who is the English teacher. In this this study the instruments were Observation Field Note and Questionnaires. The steps of data collection procedure were field note, questionnaire, and observation. The steps of data analysis in this study were data reduction and data display. The results of study showed that the students were able to perform a desired action even when there was interference or other alternative actions provided to them as a result of the process of managing willingness, as discussed in this framework. Results of the questionnaire clearly demonstrated the perceptions of the students in class 7-I at SMPN 54 Surabaya regarding the implementation of the use of volitional strategy in the academic year 2020/2021, as demonstrated by the fact that a large number of the 20 students agreed with the collected data taken from the questionnaire items.